2012
DOI: 10.1007/s12011-012-9438-1
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Modulates Cancer Cell Growth, Apoptosis, Gene Expression and Cytokine Production in HL-60 Promyelocytic Leukaemia Cells and Their Drug-Resistant Sub-clones

Abstract: Lithium has been an FDA-approved and preferred drug for the treatment of mood disorders for many years, and cumulative evidence has pointed towards its potential use as an anti-cancer agent. Previous studies in our laboratory have demonstrated that lithium induces apoptotic cell death in HL-60 promyelocytes at concentrations of 10 mM and above. A lithium-tolerant HL-60 sub-clone, resistant to up to 15 mM lithium, was also generated and its growth profile reported. Treatment of cells with lithium resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Similarly, other studies have shown that high doses of lithium (50 and 100 mM) increases apoptosis through activation of caspase‐2 and ‐7 in caspase‐3‐deficient MCF‐7 cells [Suganthi et al, ]. Furthermore, lithium has been shown to inhibit cellular proliferation in combination with the regulation of the expression of genes involved not only with the apoptosis signaling pathway [Zhang et al, ] but also with the production of inflammatory cytokines [Matsebatlela et al, ] . In CRC, lithium induced apoptosis through a mechanism that is independent of p53 activity with increased production of TNF‐α and FasL, two death‐receptor ligands that activate the extrinsic apoptosis pathway [Kaufmann et al, ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, other studies have shown that high doses of lithium (50 and 100 mM) increases apoptosis through activation of caspase‐2 and ‐7 in caspase‐3‐deficient MCF‐7 cells [Suganthi et al, ]. Furthermore, lithium has been shown to inhibit cellular proliferation in combination with the regulation of the expression of genes involved not only with the apoptosis signaling pathway [Zhang et al, ] but also with the production of inflammatory cytokines [Matsebatlela et al, ] . In CRC, lithium induced apoptosis through a mechanism that is independent of p53 activity with increased production of TNF‐α and FasL, two death‐receptor ligands that activate the extrinsic apoptosis pathway [Kaufmann et al, ].…”
Section: Discussionmentioning
confidence: 82%
“…In cancer, lithium acts as an anti-cancer agent alone [Matsebatlela et al, 2012] or auxiliary to chemotherapy and radiotherapy [Gupta et al, 2014]. Lithium is a reversible inhibitor of GSK-3b with an IC50 of 2 mM and acts by both directly competing with Mg2þ to reduce the Mg2þ ATP-dependent kinase activity of GSK-3b and indirectly reducing phosphatase activity to increase the inactive form of GSK-3-b [Gupta et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Li is an effective medication for the treatment of BD , and several studies suggest that Li exerts anti‐inflammatory effects [e.g., suppression of cyclooxygenase‐2 expression, inhibition of IL‐1β and TNF‐α production, and enhancement of IL‐2 and IL‐10 synthesis ]. However, some studies indicate that, under certain experimental conditions, Li also exhibits pro‐inflammatory properties [e.g., induction of the synthesis of IL‐4, IL‐6 and other pro‐inflammatory cytokines ]. Furthermore, a clinical study that assessed serum proteins in patients with BD demonstrated that the concentrations of IL‐10 were higher in patients in remission after mania whereas the concentrations of IFN‐γ were higher in those in remission after depression as compared to healthy controls .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both apoptosis [55] and tau-phosphorylation in those residues [56] occur naturally during development and aging. It is also known that LiCl treatment can play different roles depending on cell type, system and developmental stage [57] [58] [59] [60]. In a developmental changing scenario, where neuron pathways are being formed and connection refinement is necessary [55], opposing effects on apoptotic pathways may be observed.…”
Section: Discussionmentioning
confidence: 99%